A Habituation-Based Learning Model for Islamic Religious Education and Character Building to Strengthen Students' Religious Character at MTs Darul Hikmah Burneh, Bangkalan - Zainal Hakim (CV. Edujavare Publishing, 2026)
Students’ religious character constitutes a strategic concern in madrasah education, particularly as the younger generation faces various symptoms of moral decline. At the same time, Islamic Religious Education (PAI) and Character (Budi Pekerti) learning frequently remains confined to the cognitive domain, so that students do not necessarily translate their knowledge into everyday moral action. Departing from this problem, the study aims to develop and describe a habituation-based PAI and Budi Pekerti learning model to strengthen students’ religious character at MTs Darul Hikmah, Burneh District, Bangkalan Regency. A descriptive qualitative approach was employed, combining library research with a preliminary field study consisting of observation and document review at the research site. Data were analyzed through data reduction, data display, and conclusion drawing in accordance with the interactive model of Miles and Huberman. The findings formulate a habituation-based learning model in three stages: planning, which integrates religious values into learning devices; implementation, which comprises daily, weekly, and monthly habituation activities combining the dimensions of moral knowing, moral feeling, and moral action; and evaluation, which relies on authentic assessment through attitude observation, daily journals, and spiritual portfolios. The model is supported by pesantren culture, teacher exemplariness, and parental synergy, yet faces obstacles such as students’ heterogeneous backgrounds and limited supervision beyond the madrasah, making sustained synergy among the madrasah, the pesantren, and parents indispensable. Accordingly, the habituation model proves capable of systematically uniting Lickona’s three character dimensions within a single cycle of planning, implementation, and evaluation. The model may serve as a practical reference for PAI and Budi Pekerti teachers in designing instruction that sustainably cultivates students’ religious habits and awareness, while opening space for further empirical testing